Color Fine‐Tuning of Optical Materials Through Rational Design. Issue 5 (2nd February 2017) - Holzer, Brigitte; Bintinger, Johannes; Lumpi, Daniel; Choi, Christopher; Kim, Youngwan; Stöger, Berthold; Hametner, Christian; Marchetti‐Deschmann, Martina; Plasser, Felix; Horkel, Ernst; Kymissis, Ioannis; Fröhlich, Johannes
Abstract: We report on the feasibility for color fine‐tuning of optical materials using rational design principles based on chemical reasoning. For this purpose, a modular framework for the construction of symmetrical cap‐linker‐cap compounds, using triarylamine caps and oligothiophene linkers, is applied. The chosen structural scaffolds are heavily used in recent industrial applications and provide five possibilities for altering their electronic and steric properties: electron donor/acceptor groups, planarization/deplanarization, and modulation of the π‐conjugation length. Permutation of the used building blocks leads to a set of 54 different molecules, out of which 32 are synthesized and characterized in solution as well as in example fabricated OLED devices. This setup allows for color fine‐tuning in the range of 412 nm to 540 nm with typical steps of 4 nm. In addition, to further benefit from the large experimental data set the spectroscopic results are used to benchmark quantum chemical computations, which show excellent agreement thus highlighting the potential of these calculations to guide future syntheses. Abstract : Rational Colors : Computational chemistry guided rational design for color tuning of organic light‐emitting diode (OLED) materials is demonstrated. Through variation of the electronic and steric properties, the emission wavelength of OLED materials can be tuned in the range of 412–540 nm.